An Investigation on The Cooperative Maxims in D.H. Lawrence’s Short Story of the “Rocking Horse Winner” - Suswanto Ismadi Megah; Sri Sugiharti; Mulva Dessa Ariesti; Tri Artanto; Zulida Abdul Kadir; Saira Kazmi (UIN Salatiga, 2024)
This study aimed to investigate main issue of the maxims used in the short story The Rocking Horse Winner by DH Lawrence is a story that tells the story of a woman, Hester's dissatisfaction with her family's economic situation which triggers other problems. This study contributes in improving pragmatic study, particularly cooperative maxims used to identify how certain type applied in daily communicative realized inside the Short Story of the “Rocking Horse Winner”. Basically, this research is qualitative. The type of research that focuses on